Two new species and a new synonym in the Pardosa nebulosa-group (Lycosidae: Pardosa) from China - Wang, Dong; Zhang, Zhi-Sheng (Zootaxa, 2014)
The Pardosa nebulosa-group consists of at least 66 species, including 14 species recorded from the South China. In this paper, we describe two new species of this group, P. tuberosa sp. nov. and P. parathompsoni sp. nov. from Yunnan Province of China. Also, P. shuangjiangensis Yin et al., 1997 is newly synonymised with P. pusiola (Thorell, 1891), based on the examination of specimens mainly from Yunnan. Detailed figures and photos of genitalia, photos of habitus of these three species and SEM photos of male bulb of P. pusiola are given.